The Oncogenic Functions of MASTL Kinase - Marzec, Kamila; Burgess, Andrew (Frontiers in Cell and Developmental Biology, 2018)
MASTL kinase is a master regulator of mitosis, essential for ensuring that mitotic substrate phosphorylation is correctly maintained. It achieves this through the phosphorylation of alpha-endosulfine and subsequent inhibition of the tumour suppressor PP2A-B55 phosphatase. In recent years MASTL has also emerged as a novel oncogenic kinase that is upregulated in a number of cancer types, correlating with chromosome instability and poor patient survival. While the chromosome instability is likely directly linked to MASTL’s control of mitotic phosphorylation, several new studies indicated that MASTL has additional effects outside of mitosis and beyond regulation of PP2A-B55. These include control of normal DNA replication timing, and regulation of AKT/mTOR and Wnt/β-catenin oncogenic kinase signalling. In this review, we will examine the phenotypes and mechanisms for how MASTL, ENSA and PP2A-B55 deregulation drives tumour progression and metastasis. Finally, we will explore the rationale for the future development of MASTL inhibitors as new cancer therapeutics.